The economics of exchange rates - Sarno, Lucio; Taylor, Mark P. (Cambridge, UK ; New York, NY : Cambridge University Press, 2002)
This volume provides a selective coverage of the literature on exchange rates, focusing on developments from within the last fifteen years. Clear explanations of theories are offered, alongside an appraisal of the literature and suggestions for further research and analysis.
Includes bibliographical references and indexes.
oif 26/08/15
Loans
Keywords: Foreign exchange rates